Composite phase-change material based on volume-shrinkage-resistant photo-thermal carbon aerogel and preparation method of composite phase-change material
By using guar gum and sodium alginate to prepare antibody volume shrinkage photothermal carbon aerogel, and by vacuum impregnation of adsorbed phase change materials, the problems of energy loss and volume shrinkage of composite phase change materials during the photothermal conversion process are solved, achieving efficient photothermal conversion and low-cost production.
Patent Information
- Application Number
- CN202411671514.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The existing composite phase change materials have serious energy losses and low utilization rates during the photothermal conversion process, and carbon aerogels have volume shrinkage problems, which makes production costs high.
The antibody volume shrinkage photothermal aerogel was prepared by mechanical stirring and freeze-drying using guar gum (GG) and sodium alginate (SA) as raw materials. The antibody volume shrinkage photothermal aerogel was then prepared by two-step carbonization method, and the adsorption phase change material was immersed by vacuum to improve the photothermal conversion efficiency.
The volume shrinkage rate and photothermal conversion efficiency of composite phase change materials are significantly improved, with volume shrinkage rate of 28-30%, and photothermal conversion efficiency of 88-91%, while reducing production costs.
Smart Images

Figure CN119505823A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the fields of polymer materials and photothermal conversion phase change energy storage materials, and in particular to a composite phase change material based on anti-volume shrinkage photothermal carbon aerogel and a preparation method thereof. Background Art
[0002] Organic phase change materials have the advantages of high thermal energy storage density and constant conversion temperature. They can be applied to the field of energy conversion and enrich thermal energy storage methods. Organic phase change materials can be applied to the field of photothermal conversion energy storage materials. However, organic phase change materials generally have low thermal conductivity, low light absorption and leakage problems during the solid-liquid phase change process. Therefore, when directly applied to photothermal conversion energy storage materials, there are problems of severe energy loss and low utilization rate.
[0003] In order to solve the problem of low light-to-heat conversion efficiency of composite phase change materials, a common solution is to prepare aerogels by adding materials with light-to-heat absorption effects for improvement. For example, existing document 1 (Wang C, Wang L, Liang W, et al. Enhanced light-to-thermal conversion performance of all-carbon aerogels based form-stable phase change material composites [J]. Journal of Colloid and Interface Science, 2022, 605: 60-70.) uses graphene oxide GO as a carbon aerogel matrix, adds multi-walled carbon nanotubes MWCNT as a thermally conductive and light-to-heat enhancing material, and adsorbs hexadecene amine HAD to synthesize a composite phase change material PCM. The maximum loading rate of the composite phase change material obtained using this technical solution is 90.05%, the enthalpy value is 203.1-248 J / g, and the light-to-heat conversion efficiency is as high as 88.25%. Although this solution has improved the photothermal conversion efficiency, it has the technical problem of high production cost, which is specifically reflected in two aspects: on the one hand, the raw materials used are GO and MWCNT, which are high-cost carbon materials and photothermal enhancement materials; on the other hand, such carbon aerogel-based composite materials have the problem of volume shrinkage.
[0004] For example, existing document 2 (Wang T, Wang C, Huang Z, et al. Electro-and photo-thermal energy conversion investigation of polyethylene glycol infiltrated porous carbon aerogels [J]. Journal of Energy Storage, 2023, 68: 107724.) uses citric acid CA as a cross-linking agent and sodium carboxymethyl cellulose CMC to prepare aerogels, and then carbonizes and adsorbs phase change material PEG1000 to finally obtain a PEG / CCA composite material. This technical solution obtains a composite material with photothermal conversion performance, but according to a simple calculation of the experimental data recorded in the technical solution, it can be seen that after carbonization, the volume shrinkage rate of the aerogel is 98%, that is, there is a serious volume shrinkage problem. The reason is that the purpose of introducing CA and CMC as additives in this technical solution is to improve the porosity and conductivity of carbon aerogels, that is, they do not have the effect of resisting volume shrinkage, so serious volume shrinkage occurs when preparing carbon aerogels.
[0005] In order to solve the problem of volume shrinkage of carbon aerogel, it can be improved by introducing inhibitory materials. For example, existing document 2 (Li S, Li J, Liao Y, et al. Dual-functional polyethylene glycol / graphene aerogel phase change composites with ultrahigh loading for thermal energy storage [J]. Journal of Energy Storage, 2022, 54: 105337.) uses graphene oxide GO, ascorbic acid AA and PEG4000 to fully react at 95 ° C for 5h to obtain partially reduced GO hydrogel, which is frozen by liquid nitrogen and then freeze-dried to obtain PGA, and finally PEG4000 is vacuum impregnated at 80 ° C to obtain PCCs. The adsorption amount of PEG by the obtained aerogel PGA is increased from 40 times to 89 times, that is, the adsorption amount is increased, and the specific PEG4000 loading is 86.70%; the phase change enthalpy value is 161.15 J / g, and the photothermal conversion efficiency is 85.89%. The special feature of this technical solution is that PEG4000 is used as an inhibitory material and added to the graphene oxide / ascorbic acid hydrogel to achieve the effect of reducing volume shrinkage. The anti-volume shrinkage effect of PEG4000 in this technical solution is reflected in that the volume of the hydrogel PGA obtained by adding PEG4000 is 175% of the volume of the hydrogel GA obtained without adding PEG4000. Although this technical solution achieves the improvement of the anti-volume shrinkage rate by adding an inhibitory material, since the anti-volume shrinkage ability of PEG4000 is achieved by forming hydrogen bonds between the hydroxyl groups possessed by PEG4000 itself and the oxygen-containing functional groups on the partially reduced GA, the anti-volume shrinkage of GA is achieved, that is, it only has the technical feature of forming hydrogen bonds and cannot effectively regulate the microscopic morphology, thereby determining that the anti-volume shrinkage effect of PEG4000 is poor and cannot meet the application requirements. Summary of the invention
[0006] The object of the present invention is to provide a composite phase change material based on anti-volume shrinkage photothermal carbon aerogel and a preparation method thereof.
[0007] The technical problems existing in the prior art are solved through the following principles:
[0008] 1. In addition to the characteristics of long-chain polymer materials, SA contains a large number of hydroxyl and carboxyl groups, is easily soluble in water to form colloids, and is conducive to the formation of hydrogen bonds with guar gum. It also has the characteristics of a hard carbon skeleton and flame retardant properties. Among them, SA has a hard carbon skeleton, that is, as a hard carbon source, it can improve the volume stability and structural stability of aerogels. At the same time, the flame retardant property can maintain the stability of the hard carbon skeleton of SA during high-temperature carbonization, thereby improving the anti-volume shrinkage effect;
[0009] 2. GG also has the property of dissolving in water to form colloids. It can prepare hydrogels first and then prepare aerogels. At the same time, GG can form hydrogen bonds with SA, making the two tightly connected, and the obtained aerogel structure is more regular and dense.
[0010] 3. Both GG and SA are natural biomass materials with wide sources and low prices. The carbon aerogel prepared by mixing the two has a good porous structure, which can support the high load of phase change materials, give the composite material a high energy storage density, and provide a high enthalpy value and high photothermal conversion efficiency. The hydrogen bonding between GG and SA, the capillary force of the porous structure and the lipophilicity of the carbon aerogel itself can effectively prevent the leakage of phase change materials and meet daily application needs.
[0011] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0012] A composite phase change material based on anti-volume shrinkage photothermal carbon aerogel, using guar gum GG as a soft carbon source and sodium alginate SA as a skeleton support material, which plays an anti-volume shrinkage role;
[0013] First, G / S hydrogel is prepared by mechanical stirring and mixing, and then the anti-volume shrinkage photothermal aerogel GS is prepared by freeze drying. Subsequently, the anti-volume shrinkage photothermal carbon aerogel C-GS is prepared by a two-step carbonization method, and PW is vacuum impregnated to achieve adsorption, so that the phase change material C-GS / PW based on the anti-volume shrinkage photothermal carbon aerogel can be prepared;
[0014] The volume shrinkage of the C-GS is 28-30%;
[0015] The photothermal conversion efficiency of the C-GS-PW is 88-91%.
[0016] A method for preparing a composite phase change material based on anti-volume shrinkage photothermal carbon aerogel comprises the following steps:
[0017] Step 1, preparation of anti-volume shrinkage photothermal aerogel GS, first, guar gum GG, sodium alginate SA and water meet a certain mass ratio, GG is placed in water, and mechanical stirring and pre-mixing are performed under certain conditions to obtain a GG suspension, then SA is added to the GG suspension, and mechanical stirring and mixing are continued under certain conditions to obtain a G / S mixed solution, then the G / S mixed solution is ultrasonicated under certain conditions to obtain a G / S hydrogel, and finally, the G / S hydrogel is freeze-dried under certain conditions to obtain the anti-volume shrinkage photothermal aerogel GS, referred to as GS;
[0018] In step 1, the mass ratio of GG, SA and water is 2:1:200;
[0019] In the step 1, the conditions for mechanical stirring are: a stirring speed of 300 r / min, and a stirring time of 10-20 min; the conditions for continued stirring are: a stirring speed of 650 r / min, and a stirring time of 10-12 h; the conditions for ultrasound are: an ultrasound time of 20-30 min;
[0020] In step 1, the freeze-drying conditions are: first, the G / S hydrogel is frozen at a freezing temperature of -30--35°C for a freezing time of 10-12 hours, and then the freeze-drying temperature is -55°C for a freeze-drying time of 68-72 hours;
[0021] Step 2, to prepare the volume shrinkage-resistant photothermal carbon aerogel C-GS, first, pre-treat the GS obtained in step 1 under certain conditions, and then carbonize it by a two-step carbonization method under nitrogen conditions to obtain the volume shrinkage-resistant photothermal carbon aerogel C-GS, referred to as C-GS;
[0022] In step 2, the pretreatment conditions are: the pretreatment temperature is 80° C. and the pretreatment time is 30 min;
[0023] In step 2, the two-step carbonization method is:
[0024] The conditions for the first step of carbonization are: under nitrogen, the heating rate is 5°C / min, the carbonization temperature is 400°C, and the holding time is 2h;
[0025] The conditions for the second step carbonization are: under nitrogen, the heating rate is 5°C / min, the carbonization temperature is 800°C, and the holding time is 4h;
[0026] Step 3, preparation of phase change material C-GS / PW based on anti-volume shrinkage photothermal carbon aerogel, first, under certain conditions, with PW satisfying a certain addition amount, C-GS is placed in liquid PW, and then vacuum impregnation is performed under certain conditions to obtain phase change material C-GS / PW based on anti-volume shrinkage photothermal carbon aerogel;
[0027] In step 3, the amount of PW added is 90-96wt.%;
[0028] In step 3, the condition for preparing liquid PW is that the temperature is 80°C;
[0029] In step 3, the vacuum impregnation conditions are: the impregnation temperature is 80° C., and the impregnation time is 20-24 hours.
[0030] A composite phase change material based on anti-volume shrinkage photothermal carbon aerogel, when used as a phase change material, has a phase change temperature of 33.15-51.10°C, a phase change enthalpy of 234.32-255.71 J / g, and a thermal conductivity of 0.3514-0.4366 W / (m·K).
[0031] The present invention has the following characteristics after SEM, FTIR, XRD, DSC, planar thermal conductivity instrument, anti-leakage test, simulated illumination, and optical photo comparison test:
[0032] SEM test shows that C-GS presents an interconnected honeycomb porous structure, and PW is uniformly encapsulated in the pores of C-GS;
[0033] FTIR test shows that C-GS / PW and PW have the same characteristic peaks. C-GS successfully adsorbs PW by vacuum impregnation, that is, C-GS / PW is successfully prepared, and the adsorption process is a physical effect.
[0034] XRD tests show that C-GS / PW and PW have the same characteristic peaks, and C-GS has no effect on the crystallization behavior of PW;
[0035] According to DSC test, the melting temperature of C-GS / PW is between 49.31-51.10℃, the melting enthalpy is between 236.98-255.71J / g; the crystallization temperature is between 33.15-34.33℃, and the crystallization enthalpy is between 234.32-249.19J / g;
[0036] The DSC cycle test showed that C-GS / PW had high cycle stability and thermal stability, and the enthalpy value of the cycle curve did not change significantly after 100 cycles;
[0037] The thermal conductivity test shows that C-GS / PW has good thermal conductivity, with a thermal conductivity of 0.3514-0.4366W / (m·K);
[0038] The leakage test showed that C-GS / PW had good anti-leakage performance and no leakage occurred at 80°C for 40 minutes;
[0039] According to the simulated illumination test, C-GS / PW has photothermal conversion performance, and the photothermal conversion efficiency is 88-91%;
[0040] Optical photo comparison tests show that C-GS / PW has good resistance to volume shrinkage, with a volume shrinkage rate of 28-30%.
[0041] Therefore, the present invention has the following advantages over the prior art:
[0042] 1. SA and GG can form colloids when dissolved in water, and there is a significant hydrogen bond between SA and GG, which makes the two closely connected. The flame retardancy and hard carbon properties of SA can improve the volume stability of aerogel, thereby significantly improving the volume shrinkage resistance of carbon aerogel;
[0043] 2. The interconnected honeycomb porous structure of C-GS provides a high loading rate of phase change materials. The melting enthalpy of the composite phase change material is 236.98-255.71 J / g, and the crystallization enthalpy is 234.32-249.19 J / g, which has good heat storage performance per unit mass;
[0044] 3. The interconnected three-dimensional network structure formed by hydrogen bonding between GG and SA, the capillary force and the lipophilicity of carbon aerogel provide carbon aerogel with excellent packaging performance;
[0045] 4. The carbon aerogel-based phase change material with photothermal properties prepared by the present invention has excellent thermal stability and cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 is the SEM image of C-GS;
[0047] Figure 2 This is an optical photograph of Example 1;
[0048] Figure 3 It is a light-to-heat conversion test curve diagram of C-GS, PW, Example 1 and Comparative Example 2;
[0049] Figure 4 FTIR graphs of PW, Comparative Example 3, Example 1, Example 2 and Example 3;
[0050] Figure 5 XRD patterns of PW, Comparative Example 3, Example 1, Example 2 and Example 3
[0051] Figure 6 The SEM images of Example 1, Comparative Example 3, Example 2 and Example 3 are shown;
[0052] Figure 7 DSC curves of PW, Comparative Example 3, Example 1, Example 2 and Example 3;
[0053] Figure 8 It is the DSC 100 cycle curve diagram of Example 1;
[0054] Fig. 9 is a graph of thermal conductivity of PW, comparative example 3, example 1, example 2 and example 3;
[0055] Fig.10 It is the anti-leakage test diagram of PW, comparative example 3, embodiment 1, embodiment 2 and embodiment 3;
[0056] Fig.11 This is an optical photograph of Comparative Example 1. DETAILED DESCRIPTION
[0057] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0058] Example 1
[0059] A method for preparing a composite phase change material based on anti-volume shrinkage photothermal carbon aerogel comprises the following steps:
[0060] Step 1, preparation of anti-volume shrinkage photothermal aerogel GS, first, with a mass ratio of guar gum GG, sodium alginate SA and water of 2:1:200, 2g GG is placed in 200g water, and mechanical stirring premixing is performed at a stirring speed of 300r / min and a stirring time of 10min to obtain a GG suspension, then 1g SA is added to the GG suspension, and mechanical stirring mixing is continued at a stirring speed of 650r / min and a stirring time of 12h to obtain a G / S mixed solution, and then the G / S mixed solution is ultrasonicated at an ultrasonic time of 30min to obtain a G / S hydrogel, and finally, the G / S hydrogel is first frozen at a freezing temperature of -30°C and a freezing time of 12h, and then the G / S hydrogel is freeze-dried at a freeze-drying temperature of -55°C and a freeze-drying time of 72h to obtain the anti-volume shrinkage photothermal aerogel GS, referred to as GS;
[0061] Step 2, preparation of anti-volume shrinkage photothermal carbon aerogel C-GS, first, pretreating the GS obtained in step 1 at a pretreatment temperature of 80°C and a pretreatment time of 30 min, and then carbonizing it under nitrogen by a two-step carbonization method to obtain anti-volume shrinkage photothermal carbon aerogel C-GS, referred to as C-GS;
[0062] The two-step carbonization method is:
[0063] The conditions for the first step of carbonization are: under nitrogen, the heating rate is 5°C / min, the carbonization temperature is 400°C, and the holding time is 2h;
[0064] The conditions for the second step carbonization are: under nitrogen conditions, the heating rate is 5°C / min, the carbonization temperature is 800°C, and the holding time is 4h.
[0065] In order to verify the microstructure of C-GS, SEM test was performed. Figure 1 As shown, C-GS presents an interconnected honeycomb porous structure.
[0066] In order to prove the anti-volume shrinkage effect of C-GS, the volume parameters of GS obtained in step 1 and C-GS obtained in step 2 were tested before and after carbonization. Figure 2 As shown,
[0067] Before carbonization, GS had a cylindrical structure with a diameter of 3 cm and a height of 2.7 cm;
[0068] After carbonization, C-GS maintained a cylindrical structure with a diameter of 2 cm and a height of 1.8 cm. The volume shrinkage was calculated to be 70%.
[0069] The test results show that C-GS has the property of resisting volume shrinkage.
[0070] In order to prove the photothermal conversion performance of C-GS, a simulated illumination experiment was conducted. The specific method of the simulated illumination experiment is to use a simulated light source to illuminate the sample and measure the temperature change at the same time. The test results are as follows Figure 3 As shown in the figure, C-GS heats up rapidly without a temperature control platform. The test results show that C-GS has good light-to-heat conversion performance.
[0071] Step 3, preparation of a composite phase change material C-GS / PW based on anti-volume shrinkage photothermal carbon aerogel. First, at a temperature of 80°C, with an addition amount of PW of 94wt.%, that is, the mass ratio of C-GS and PWPW obtained in step 2 is 6:94, C-GS is placed in liquid PW, and then vacuum impregnation is performed at an immersion temperature of 80°C and an immersion time of 24h to obtain a composite phase change material C-GS / PW based on anti-volume shrinkage photothermal carbon aerogel, referred to as C-GS / PW. The C-GS / PW obtained in specific Example 1 is named C-GS / PW-94.
[0072] In order to prove the composition of C-GS / PW-94, i.e., its successful preparation, FTIR test and XRD test were carried out. Meanwhile, for comparison, FTIR test and XRD test were carried out on PW.
[0073] The FTIR test results of C-GS / PW-94 and PW are as follows Figure 4 As shown, C-GS / PW-94 and PW have the same characteristic peaks;
[0074] The XRD test results of C-GS / PW-94 and PW are shown in Figure 5 As shown, C-GS / PW-94 and PW have the same characteristic peaks;
[0075] The test results show that C-GS successfully adsorbed PW through vacuum impregnation, that is, C-GS / PW-94 was successfully prepared, and the adsorption process was a physical effect; at the same time, C-GS had no effect on the crystallization behavior of PW.
[0076] In order to verify the microstructure of C-GS / PW-94, SEM test was performed. The test results are shown in Figure 6 As shown, C-GS has a pore structure, and PW is uniformly encapsulated in the pores of C-GS.
[0077] In order to prove the phase change performance of C-GS / PW-94, DSC test was carried out. At the same time, DSC test was carried out on PW for comparison. The test results are shown in Figure 2. Figure 7 As shown in Table 1,
[0078] The test results of PW are that within the test temperature range of 20-80°C, during the crystallization process of PW, there is an exothermic peak at 34.56°C with an enthalpy of 262.69 J / g; during the melting process of PW, there is an endothermic peak at 46.26°C with an enthalpy of 263.28 J / g;
[0079] The test results of C-GS / PW-94 are as follows: within the test temperature range of 20 to 80°C, during the crystallization process of C-GS / PW-94, there is an exothermic peak at 33.87°C with an enthalpy of 245.76 J / g; during the melting process of C-GS / PW-94, there is an endothermic peak at 50.11°C with an enthalpy of 251.72 J / g;
[0080] Since the amount of PW added in C-GS / PW-94 is 94wt.%, the latent heat value of C-GS / PW-94 is compared with the theoretical latent heat value of PW. The comparison result shows that C-GS / PW-94 is greater than PW. The comparison result shows that the addition of C-GS can promote the movement of PW molecular chains, thereby improving the storage and release of latent heat.
[0081] Table 1 Phase change enthalpy and temperature of composite phase change materials with different PW addition amounts
[0082]
[0083] In order to prove the cyclic stability of C-GS / PW-94, a cyclic test was performed. The test results are shown in Figure 8 As shown in the figure, the thermal cycling curve of C-GS / PW-94 has no obvious change in 100 cycles. The test results show that the phase change performance of C-GS / PW-94 has no obvious change before and after the cycle, which proves that C-GS / PW-94 has good cycle stability.
[0084] In order to prove the thermal conductivity of C-GS / PW-94, a thermal conductivity test was conducted, and for comparison, a thermal conductivity test was conducted on PW.
[0085] PW test results are as follows Fig. 9 As shown in Figure 2 and Table 2, the thermal conductivity of PW is 0.3487 W / (m·K);
[0086] The test results of C-GS / PW-94 are shown in Figure 9 and Table 2. The thermal conductivity of C-GS / PW-94 is 0.3844 W / (m·K);
[0087] The test results show that the thermal conductivity of C-GS is 10% higher than that of PW. The reason is that C-GS can form a heat conduction path and improve the thermal conductivity of C-GS / PW-94.
[0088] Table 2 Thermal conductivity of composite phase change materials with different PW addition amounts
[0089] Sample name PW Example 1 Example 2 Example 3 Comparative Example 3 Thermal conductivity (W / m·K) 0.3487 0.3844 0.4366 0.4051 0.3514
[0090] In order to prove the packaging performance of the prepared C-GS / PW-94, a leak test was conducted. At the same time, for comparison, a leak test was conducted on PW. The specific test method is to heat the sample to be tested at a heating temperature of 80°C and a heating time of 40 minutes to observe the material state.
[0091] The test results of PW are as follows Fig.10 As shown, PW completely melted and flowed around;
[0092] The test results of C-GS / PW-94 are as follows Fig.10 As shown, there was no significant change in C-GS / PW-94;
[0093] The test results show that C-GS can make C-GS / PW-94 have excellent packaging performance.
[0094] In order to prove the photothermal conversion performance of C-GS / PW-94, a simulated illumination experiment was conducted. At the same time, for comparison, a simulated illumination experiment was conducted on PW. The test results are as follows: Figure 3 As shown,
[0095] The test results of PW show that PW slowly heats up and an obvious temperature control platform appears at 41.6℃. The photothermal conversion efficiency is calculated to be 62.6%.
[0096] The test results of C-GS / PW-94 show that C-GS / PW-94 heats up rapidly and an obvious temperature control platform appears at 45°C. The photothermal conversion efficiency is calculated to be 90.22%, which proves that C-GS / PW-94 has good photothermal conversion performance.
[0097] Combined with the test results of C-GS obtained in step 2, it can be seen that C-GS can significantly enhance the photothermal conversion performance.
[0098] In order to demonstrate the effect of SA on C-GS in C-GS, Comparative Example 1 is provided, which is an aerogel CG prepared without adding SA.
[0099] Comparative Example 1
[0100] An aerogel CG prepared without adding SA, wherein the steps without particular description are the same as those in Example 1, except that: in the step 1, no SA is added, therefore, the material obtained in the step 1 is named G, and the material obtained in the step 2 is named CG.
[0101] In order to prove the anti-volume shrinkage effect of CG, the volume parameters of G obtained in step 1 and CG obtained in step 2 were tested before and after carbonization. The test results are shown in Figure 2. Fig.11 As shown,
[0102] Before carbonization, G was a cylindrical structure with a diameter of 3.5 cm and a height of 3 cm;
[0103] After carbonization, CG could not maintain its cylindrical structure, that is, there was an obvious structural collapse phenomenon, with a diameter of 1.3 cm and a height of 0.8 cm. The calculated volume shrinkage was 96.3%.
[0104] By comparison with Example 1, it can be seen that the addition of SA can significantly reduce the volume shrinkage and collapse of the aerogel during carbonization, and maintain the structure to avoid collapse;
[0105] It can be known from simple technology that the volume of C-GS is 240% of the volume of CG, which reflects the technical effect of SA as a suppressive material in the technical solution;
[0106] According to the experimental data recorded in the existing document 3, the volume enhancement rate of the PGA hydrogel in the existing document 3 is 175%, which is only 72.9% of the technical effect of the present invention;
[0107] The reason is that sodium alginate, as a hard carbon source, can not only improve the flame retardancy of the composite material by utilizing its own flame retardancy, but also improve the volume stability and structural stability of the aerogel through the hard carbon properties.
[0108] Therefore, it can be seen from Example 1 and Comparative Example 1 that SA can effectively improve the volume shrinkage resistance of C-GS aerogel.
[0109] In order to demonstrate the effect of carbonization in step 2, comparative example 2 is provided, which is a GS / PW prepared by directly adsorbing PW with GS without carbonization.
[0110] Comparative Example 2
[0111] A method for preparing GS / PW, wherein the steps not specified are the same as those in Example 1, except that step 2 is not required, and in step 3, GS is used instead of C-GS. The obtained material is named GS / PW.
[0112] The photothermal conversion performance test results of GS / PW are as follows: Figure 4 As shown in the figure, the GS / PW temperature rises slowly, the highest temperature reached by illumination under the same conditions is less than 50°C, and the photothermal platform has not ended, so the photothermal conversion efficiency cannot be calculated. The test results show that carbonization can effectively improve the photothermal conversion efficiency of aerogels.
[0113] In order to demonstrate the effect of the amount of PW added on the performance of C-GS / PW, Example 2, Example 3 and Comparative Example 2 are provided, and the amount of PW added is 90 wt.%, 92 wt.%, respectively, to prepare supersaturated C-GS / PW.
[0114] Example 2
[0115] A method for preparing C-GS / PW with a PW addition amount of 90 wt.%, wherein the steps without particular description are the same as those in Example 1, except that in step 3, the PW addition amount is 90 wt.%, and the obtained material is named C-GS / PW-90.
[0116] The FTIR test results of C-GS / PW-90 are as follows Figure 4 As shown, the infrared characteristic peaks of FTIR of C-GS / PW-90 are the same as those of C-GS / 94, with no obvious changes;
[0117] XRD test of C-GS / PW-90 Figure 5 As shown, the XRD characteristic diffraction peaks of C-GS / PW-90 are the same as those of C-GS / PW-94, and there is no obvious change;
[0118] Therefore, there is no substantial difference between C-GS / PW-90 and C-GS / PW-94.
[0119] SEM test of C-GS / PW-90 Figure 6 As shown in the figure, PW is uniformly encapsulated in the pores of C-GS, but there are still exposed pore structures. The reason is that the amount of PW added has not reached saturation.
[0120] The DSC test results of C-GS / PW-90 are as follows Figure 7 As shown in Table 1, within the test temperature range of 20-80°C, the melting process of C-GS / PW-90 has an endothermic peak at 51.10°C with an enthalpy of 236.98 J / g, and the crystallization process has an exothermic peak at 33.15°C with an enthalpy of 234.32 J / g.
[0121] The thermal conductivity test results of C-GS / PW-90 are as follows: Fig. 9 As shown in Table 2, the thermal conductivity of C-GS / PW-90 is 0.4366 W / (m·K).
[0122] The packaging performance test results of C-GS / PW-90 are as follows: Fig.10 As shown, there is no obvious change in C-GS / PW-90. The test results show that C-GS has excellent packaging performance and can effectively prevent PW leakage.
[0123] Example 3
[0124] A method for preparing C-GS / PW with a PW addition amount of 92 wt.%, wherein the steps without particular description are the same as those in Example 1, except that in step 3, the PW addition amount is 92 wt.%, and the obtained material is named C-GS / PW-92.
[0125] The FTIR test results of C-GS / PW-92 are as follows Figure 4 As shown, the infrared characteristic peaks of FTIR of C-GS / PW-92 are the same as those of C-GS / 94, with no obvious changes;
[0126] XRD test of C-GS / PW-92 Figure 5 As shown, the XRD characteristic diffraction peaks of C-GS / PW-92 are the same as those of C-GS / PW-94, and there is no obvious change;
[0127] Therefore, there is no substantial difference between C-GS / PW-92 and C-GS / PW-94.
[0128] SEM test of C-GS / PW-92 Figure 6As shown in the figure, PW is uniformly encapsulated in the pores of C-GS, but there are still exposed pore structures. The reason is that although the amount of PW added in C-GS / PW-92 is increased compared with C-GS / PW-90, it still has not reached saturation.
[0129] The DSC test results of C-GS / PW-92 are as follows Figure 7 As shown in Table 1, within the test temperature range of 20-80°C, the melting process of C-GS / PW-92 has an endothermic peak at 50.45°C with an enthalpy of 249.61 J / g, and the crystallization process has an exothermic peak at 33.75°C with an enthalpy of 240.12 J / g.
[0130] The thermal conductivity test results of C-GS / PW-92 are as follows: Fig. 9 As shown in Table 2, the thermal conductivity of C-GS / PW-92 is 0.4051 W / (m·K).
[0131] The packaging performance test results of C-GS / PW-92 are as follows Fig.10 As shown, C-GS / PW-92 has no obvious change. The test results show that C-GS has excellent packaging performance and can effectively prevent PW leakage.
[0132] Comparative Example 3
[0133] A method for preparing C-GS / PW with supersaturated PW addition, wherein the steps without particular description are the same as those in Example 1, except that: in the step 3, C-GS is immersed in excess PW for vacuum adsorption to obtain C-GS / PW with supersaturated PW addition, and the masses of C-GS before adsorption and C-GS / PW after adsorption are weighed and calculated to obtain the adsorption amount of paraffin. The calculation result shows that the adsorption amount of C-GS / PW obtained in Comparative Example 3 is 96.12%. Therefore, the material obtained in Comparative Example 3 is named C-GS / PW-96.
[0134] The FTIR test results of C-GS / PW-96 are as follows Figure 4 As shown, the infrared characteristic peaks of FTIR of C-GS / PW-96 are the same as those of C-GS / 94, with no obvious changes;
[0135] XRD test of C-GS / PW-96 Figure 5 As shown, the XRD characteristic diffraction peaks of C-GS / PW-96 are the same as those of C-GS / PW-94, and there is no obvious change;
[0136] Therefore, there is no substantial difference between C-GS / PW-96 and C-GS / PW-94.
[0137] SEM test of C-GS / PW-96 Figure 6 As shown in the figure, although PW is still uniformly encapsulated in the pores of C-GS, the pore structure has been completely filled and the skeleton structure cannot be seen. The test structure shows that the PW addition has reached saturation.
[0138] The DSC test results of C-GS / PW-96 are as follows Figure 7 As shown in Table 1, within the test temperature range of 20 to 80°C, the melting process of C-GS / PW-96 has an endothermic peak at 49.31°C with an enthalpy of 255.71 J / g, and the crystallization process has an exothermic peak at 34.33°C with an enthalpy of 249.19 J / g.
[0139] The thermal conductivity test results of C-GS / PW-96 are as follows: Fig. 9 As shown in Table 2, the thermal conductivity of C-GS / PW-96 is 0.3514 W / (m·K).
[0140] The leakage test results of C-GS / PW-96 are as follows Fig.10 As shown, C-GS / PW-96 has leakage.
[0141] Combining the macroscopic phenomenon SEM test and anti-leakage test results, it can be seen that the adsorption amount of C-GS / PW-96 is in a supersaturated state.
[0142] Through Example 1, Example 2, Example 3 and Comparative Example 3, the following conclusions can be obtained:
[0143] 1. When the addition amount of PW is less than 96.12wt.%, with the increase of PW addition amount, the enthalpy value of C-GS / PW increases and the thermal conductivity decreases, but it still meets the daily high enthalpy application requirements;
[0144] 2. When the addition amount of PW is greater than or equal to 96.12wt.%, C-GS / PW reaches saturation, leakage occurs, and the application requirements are not met;
[0145] Therefore, the addition amount of PW should be 90-96 wt.%.
Claims
1. A composite phase change material based on anti-volume shrinkage photothermal carbon aerogel, characterized by: Guar gum GG, a soft carbon source, is used as raw material, and sodium alginate SA is used as a skeleton support material to resist volume shrinkage. First, G / S hydrogel is prepared by mechanical stirring and mixing, and then the anti-volume shrinkage photothermal aerogel GS is prepared by freeze-drying. Subsequently, the anti-volume shrinkage photothermal carbon aerogel C-GS is prepared by a two-step carbonization method. PW is vacuum impregnated to achieve adsorption, and the composite phase change material C-GS / PW based on the anti-volume shrinkage photothermal carbon aerogel is prepared.
2. The composite phase change material based on anti-volume shrinkage photothermal carbon aerogel according to claim 1, characterized in that: The volume shrinkage of the C-GS is 28-30%.
3. The composite phase change material based on anti-volume shrinkage photothermal carbon aerogel according to claim 1, characterized in that: The photothermal conversion efficiency of the C-GS-PW is 88-91%.
4. A method for preparing a composite phase change material based on anti-volume shrinkage photothermal carbon aerogel, characterized in that The following steps are involved: Step 1, preparation of anti-volume shrinkage photothermal aerogel GS, first, guar gum GG, sodium alginate SA and water meet a certain mass ratio, GG is placed in water, and mechanical stirring and pre-mixing are performed under certain conditions to obtain a GG suspension, then SA is added to the GG suspension, and mechanical stirring and mixing are continued under certain conditions to obtain a G / S mixed solution, then the G / S mixed solution is ultrasonicated under certain conditions to obtain a G / S hydrogel, and finally, the G / S hydrogel is freeze-dried under certain conditions to obtain the anti-volume shrinkage photothermal aerogel GS, referred to as GS; Step 2, preparation of volume shrinkage-resistant photothermal carbon aerogel C-GS, first, pre-treating the GS obtained in step 1 under certain conditions, and then carbonizing it by a two-step carbonization method under nitrogen conditions to obtain volume shrinkage-resistant photothermal carbon aerogel C-GS, referred to as C-GS; Step 3, preparation of phase change material C-GS / PW based on anti-volume shrinkage photothermal carbon aerogel. First, under certain conditions, with PW satisfying a certain addition amount, C-GS is placed in liquid PW, and then vacuum impregnation is performed under certain conditions to obtain phase change material C-GS / PW based on anti-volume shrinkage photothermal carbon aerogel.
5. The preparation method according to claim 4, characterized in that: In the step 1, the mass ratio of GG, SA and water is 2:1:200; In step 3, the amount of PW added is 90-96 wt.%.
6. The preparation method according to claim 4, characterized in that: In the step 1, the conditions for mechanical stirring are: a stirring speed of 300 r / min, and a stirring time of 10-20 min; the conditions for continued stirring are: a stirring speed of 650 r / min, and a stirring time of 10-12 h; the conditions for ultrasound are: an ultrasound time of 20-30 min; In step 1, the freeze-drying conditions are: first, the G / S hydrogel is frozen at a freezing temperature of -30--35°C for a freezing time of 10-12 hours, and then the freeze-drying temperature is -55°C for a freeze-drying time of 68-72 hours; In step 2, the pretreatment conditions are: the pretreatment temperature is 80° C. and the pretreatment time is 30 min.
7. The preparation method according to claim 4, characterized in that: In step 2, the two-step carbonization method is: The conditions for the first step of carbonization are: under nitrogen, the heating rate is 5°C / min, the carbonization temperature is 400°C, and the holding time is 2h; The conditions for the second step carbonization are: under nitrogen conditions, the heating rate is 5°C / min, the carbonization temperature is 800°C, and the holding time is 4h.
8. The preparation method according to claim 4, characterized in that: In step 3, the condition for preparing liquid PW is that the temperature is 80°C; In step 3, the vacuum impregnation conditions are: the impregnation temperature is 80° C., and the impregnation time is 20-24 hours.
9. A composite phase change material based on anti-volume shrinkage photothermal carbon aerogel, characterized by: When used as a phase change material, the phase change temperature is 33.15-51.10°C, the phase change enthalpy is 234.32-255.71 J / g, and the thermal conductivity is 0.3514-0.4366 W / (m·K).